Legal regulation of intellectual property in sports - Iasechko, Svitlana; Zaitsev, Oleksii; Pokusa, Filip; Saienko, Volodymyr; Harashchuk, Ilona (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Exploitation of intellectual property rights in the field of sports is currently one of the most powerful sources of funding for sports, sports activities, and various sports events. However, unfortunately the sports organizations and individual right holders encounter problems regarding protection issues. There is a strong need to ensure the protection of these rights, and strengthen their potential to generate income from them. The use of intellectual property in modern conditions is a significant financial asset of the sports sphere. When acquiring rights of intellectual property, sports organizations, athletes and other rights holders often feel the need for legal regulation, protection and commercialization of intellectual property, as this is a prerequisite for their further profitable use. Hence, the present research aimed to study peculiarities of legal support, implementation and protection of intellectual property rights in the field of sports.